Congenital lipodystrophy (Seip syndrome) in Sri Lanka - de Silva, D.G.H. (Sri Lanka Medical Association, 1984)
No abstract available
Indexed in MEDLINE
Keywords: Lipodystrophy-congenital; Lipodystrophy-genetics